Food insecure households faced greater challenges putting healthy food on the table during the COVID-19 pandemic in Australia. (1st February 2022) - Kent, Katherine; Murray, Sandra; Penrose, Beth; Auckland, Stuart; Godrich, Stephanie; Lester, Elizabeth; Visentin, Denis
Abstract: The COVID-19 pandemic negatively affected the Australian food supply. However, it has remained unclear how food access, food availability and consumption were impacted, especially for households experiencing food insecurity. This study aimed to determine the association between food security and cooking and eating habits, food access and availability, self-sufficiency and perceptions of the food supply at the beginning of the COVID-19 pandemic in Tasmania, Australia. Throughout May–June 2020 during strict social distancing restrictions, a cross-sectional survey was conducted including the U.S. Household Food Security Survey Module Six-Item Short Form, twenty Likert scale questions on cooking and eating habits, food access, self-sufficiency and perceptions of the food supply (responses from 1 = strongly agree to 5 = strongly disagree), two questions on food availability and eleven socio-demographic questions. Survey data (n = 1067) were analysed using multivariate linear regression, and binary logistic regression. Food insecure households were significantly more likely to agree they were consuming less fresh food compared with food secure households (Mean difference between scale responses (MD) = 0.66; 95%CI:0.36–0.66; p < 0.001), and significantly more food insecure households agreed it was more difficult to get to the shops (MD = 0.49; 95%CI:0.34–0.64; p < 0.001) and they had less money available for food than prior to the COVID-19 pandemic (MD = 0.95; 95%CI:0.79–1.10; p < 0.001). Compared to food secure households, food insecure households were at significantly greater risk of foods being unavailable to them (OR:1.75; 95%CI:1.33–2.35; p < 0.001) and were less likely to have sufficient food stored in their homes (OR:0.48; 95%CI: 0.33–0.687; p < 0.001). This study indicates there was a disproportionate impact of the COVID-19 pandemic on food insecure households, related to food availability and access, with effects on cooking and eating habits.